SYARIAH BONDS: BETWEEN THEORY AND IMPLICATIONS - Noor Iffatin Nadhifah, Siti Imania Muflihatin (STAI AL-HIDAYAT Lasem, 2024)
Sukuk is one of the investment alternatives for investors who want to invest in securities. valuable. Similar to conventional debt securities or bonds, sukuk are also traded in the capital market called the Sharia Capital Market. The Sharia Capital Market is a capital market like the conventional securities capital market as regulated in the UUPM (Capital Market Law), but there is an additional requirement that this capital market must not conflict with Islamic law. Sukuk is different from bonds. This difference can be seen from the absence of a fixed interest rate as a reward for investors as in bonds. Fixed interest rates in Islamic law are prohibited because they are usury. The most fundamental difference between sukuk and bonds is the absence of an effective interest rate as a reward. In addition, sukuk only circulates in the business of companies that comply with Islamic law or companies that do not violate Islamic law.